2014
DOI: 10.1002/anie.201306489
|View full text |Cite
|
Sign up to set email alerts
|

CH Bond Functionalization through Intramolecular Hydride Transfer

Abstract: Known for over a century, reactions that involve intramolecular hydride-transfer events have experienced a recent resurgence. Undoubtedly responsible for the increased interest in this research area is the realization that hydride shifts represent an attractive avenue for C-H bond functionalization. The redox-neutral nature of these complexity-enhancing transformations makes them ideal for sustainable reaction development. This Review summarizes recent progress in this field while highlighting key historical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
91
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 291 publications
(93 citation statements)
references
References 189 publications
(164 reference statements)
1
91
0
1
Order By: Relevance
“…As part of our ongoing efforts to develop practical methods for the C–H functionalization of amines, 3 , 4 we recently reported the first examples of what may be termed a redox-annulation of amines ( Scheme 2 ). 3b Conceptually, an amine such as THIQ engages an aldehyde with a pendent carbon nucleophile to form product 2 via reductive N -alkylation/oxidative C–C bond formation in an overall redox-neutral process.…”
Section: Introductionmentioning
confidence: 99%
“…As part of our ongoing efforts to develop practical methods for the C–H functionalization of amines, 3 , 4 we recently reported the first examples of what may be termed a redox-annulation of amines ( Scheme 2 ). 3b Conceptually, an amine such as THIQ engages an aldehyde with a pendent carbon nucleophile to form product 2 via reductive N -alkylation/oxidative C–C bond formation in an overall redox-neutral process.…”
Section: Introductionmentioning
confidence: 99%
“…It was further confirmed by the unidirectional conversion of 3a to 4a (eqs S4 and S5). Moreover, intermediate 7a was confirmed in this reaction, and labeling experiments using 18 O-DMSO showed that the oxygen atom of 7a originates from DMSO. The detected ammonia suggested that the nitrogen atom of 1a is converted into ammonia (eqs S6 and S7).…”
mentioning
confidence: 74%
“…Direct introduction of chirality far from the pre‐existed chiral centers within linear compounds is relatively challenging and alluring. Remote chirality transfer through intramolecular hydride transfer has been developed and utilized in synthesis of complex molecules including natural products . However, examples on this type of chirality transfer through formation of medium cycle to install new chiral centers and generate new molecular scaffold are rare.…”
Section: Introductionmentioning
confidence: 99%